The Importance of Teaching Resources on Physical Sciences Learners’ Academic Achievement in Rural Schools: A Case of South Africa - Zenda, Rekai (Social Education Research, 2024)
The purpose of the article is to explore the importance of teaching resources on the academic achievement of physical science learners in selected rural secondary schools. Qualitative research was undertaken and data were collected from physical sciences teachers, principals and curriculum advisers, through in-depth face-to-face interviews. A multiple-case study design was used and the Activity Theory acts as a theoretical lens, offering a broad approach to analysing the availability of instructional resources and the context of teaching and learning in rural secondary schools. The study revealed three important aspects: resource availability, the quality of textbooks and the value of information, communication and technology (ICT). The availability and quality of resources were found to impact the effectiveness of science teaching in rural schools significantly. The resources make it possible for learners to do practical work, which could contribute to comprehension and possibly improve learner’s performance. It is therefore recommended that the Department of Basic Education should address interlocking frameworks for change that include, providing Curriculum Assessment Policy Statements (CAPS) aligned textbooks, well-equipped laboratories, use of ICT and develop teachers’ skills and knowledge in rural secondary schools.